Enhancing Learning: Peer Assessment's Influence on English as a Foreign Language Education in Indonesia - Prastikawati, Entika Fani; Adeoye, Moses Adeleke (Universitas Pendidikan Ganesha, 2024)
The increasing demand for English talent in the worldwide arena, educational systems need to discover effective techniques to beautify language learning. Peer assessment is one approach that can improves students' language abilities. Therefore, this research paper examines the influence of peer assessment on English as a Foreign Language (EFL) education in Indonesia. This study employs a descriptive qualitative approach. Data gathered using observations, structured interviews and document analysis. The collected data are analyzed using a thematic approach. The result found that teachers continue to explore revolutionary pedagogical methods, integrating peer assessment into EFL classrooms can empower students to grow to be extra autonomous and gifted language novices. By embracing the concepts of peer assessment, Indonesia can further improve its role as a hub for English language training and equip its youngsters with the abilities necessary to thrive in a globalized society. In conclusion, peer assessment has the potential to significantly beautify EFL education in Indonesia through energetic learning, fostering language proficiency, and cultivating a culture of collaboration and communication.